Optimizing reduced graphene oxide aerogel for a supercapacitor - Poh Lee, Soon; Gomaa, A.M. Ali; H.H., Hegazy; Lim, Hong Ngee; Chong, Kwok Feng (ACS Publication, 2021)
Reduce graphene oxide (rGO) aerogels with different precursor graphene oxide sheet sizes are synthesized using L-ascorbic acid reduction followed by an ambient pressure drying method. The sheet sizes determine the oxygen functionality content during aerogel formation, which subsequently affect its structural properties. The optimized sheet size renders strong parallel sheet stacking to provide mechanical strength that withstands capillary action during aerogel formation with a high surface area (190.40 m2 g−1) and pore volume (0.261 cm3 g−1). Such surface properties enhance the electrochemical properties of rGO aerogel (182 F g−1 at 0.75 A g−1) and render it to be an excellent electrode material for a supercapacitor.